Kynurenines and aerobic exercise capacity in chronic kidney disease: A cross-sectional and longitudinal study. - Helena Wallin; Eva Jansson; Sophie Erhardt; Carin Wallquist; Britta Hylander; Stefan H Jacobson; Kenneth Caidahl; Anette Rickenlund; Maria J Eriksson (PLoS ONE)
Background The causes of reduced aerobic exercise capacity (ExCap) in chronic kidney disease (CKD) are multifactorial, possibly involving the accumulation of tryptophan (TRP) metabolites such as kynurenine (KYN) and kynurenic acid (KYNA), known as kynurenines. Their relationship to ExCap has yet to be studied in CKD. We hypothesised that aerobic ExCap would be negatively associated with plasma levels of TRP, KYN and KYNA in CKD. Methods We included 102 patients with non-dialysis CKD stages 2-5 (CKD 2-3, n = 54; CKD 4-5, n = 48) and 54 healthy controls, age- and sex-matched with the CKD 2-3 group. ExCap was assessed as peak workload during a maximal cycle ergometer test. Plasma KYN, KYNA and TRP were determined by high-performance liquid chromatography. Kidney function was evaluated by glomerular filtration rate (GFR) and estimated GFR. The CKD 2-3 group and healthy controls repeated tests after five years. The association between TRP, KYN, KYNA and ExCap in CKD was assessed using a generalised linear model. Results At baseline, there were significant differences between all groups in aerobic ExCap, KYN, KYNA, TRP and KYN/TRP. KYNA increased in CKD 2-3 during the follow-up period. In CKD 2-5, KYNA, KYN/TRP and KYNA/KYN were all significantly negatively associated with ExCap at baseline, whereas KYN and TRP were not. Kynurenines were significantly correlated with GFR (p < 0.001 for all). Including GFR in the statistical model, no kynurenines were independently associated with ExCap at baseline. At follow-up, the increase in KYN and KYN/TRP was related to a decrease in ExCap in CKD 2-3. After adjusting for GFR, increase in KYN/TRP remained an independent significant predictor of a decline in ExCap in CKD 2-3. Conclusion Aerobic ExCap was inversely associated with plasma levels of kynurenines in CKD at baseline and follow-up.